Deciphering the bio-stimulants induced alterations in the growth of citrus (Citrus spp.) rootstocks though multivariate analysis - KOUR, MANDEEP; BAKSHI, PARSHANT; KOUR, KIRAN; SINGH, BRAJESHWAR; BHUSHAN, BHARAT; KOUR, SARABDEEP; CHOUDHARY, ASHIMA; SINGH, VIKRAMJIT; DAHIYA, PRIYANKA (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2022 and 2023 at Research Farm, Sher-e-Kashmir University of Agricultural Sciences and Technology of Jammu, Chatha, Jammu, Jammu and Kashmir to study the correlation and principal component analysis in eight different citrus (Citrus spp.) rootstocks. The experiment was laid in factorial completely randomized design (FCRD) with four distinct plant growth-promoting rhizobacteria (PGPRs), viz. P1 (Bacillus subtilis); P2 (Pseudomonas fluorescens); P3 (consortia-Bacillus subtilis + Pseudomonas fluorescens); P4 (control) and eight distinct citrus rootstocks, viz. R1 (Rough lemon); R2 (Carrizo citrange); R3 (Rangpur lime); R4 (Goutoucheng); R5 (Sun Chu Sha); R6 (Swingle citrumelo); R7 (Troyer citrange) and R8 (Volkamer lemon) which were replicated thrice. The results of the investigation revealed that seedling height was positively correlated with stem girth (0.5510), root:shoot ratio (0.0399), chlorophyll content (0.5426) and leaf area (0.369) whereas, dry weight of leaves was negatively and significantly correlated with days taken for germination (-0.8693). Germination percentage was positively correlated with fresh (0.5816) and dry weight of shoots (0.5986). Moreover, chlorophyll content was negatively correlated with root: shoot ratio (-0.0912), leaf area (-0.2041) and days taken for germination (-0.1168) while, it was positively correlated with fresh leaf biomass (0.3533) and dry leaf biomass (0.3537). In principal component analysis, days taken for germination, seedling height (90 DAS) and chlorophyll content (90 DAS) showed positive contribution (PC2) whereas, number of secondary roots, dry weight of root and leaf area showed negative contribution.